PENERAPAN PEMBELAJARAN JARAK JAUH BERBASIS E-LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Handri Wijaya; Riska Hanita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Mathematical reasoning ability is a vital aspect that must be possessed by students in understanding mathematical problems. With the ability to reason students can analyze new situations, make logical assumptions, explain ideas and make conclusions. Mathematical reasoning abilities can be developed using learning models that are able to open students' horizons. However, in the midst of the COVID-19 pandemic, there are limitations in terms of the learning process, thus distance learning based on e-learning is one of the choices of learning models that can be applied in schools. This study will discuss whether there are differences in students' mathematical reasoning abilities between before and after e-learning-based Distance Learning. In this study using ex post facto research methods, where the population in this study were all class VII students of MTs Ma'arif Bugel An-Nur in Indramayu with the research sample being class VII A students. The research instrument used in this study was a test of reasoning ability. mathematics (pretest and posttest) and non-test in the form of a mathematical disposition questionnaire. The collected data were analyzed using SPPS Statistic 20 software and Ms. Excel. Analysis of the data used was the Wilcoxon test from the results of the pretest and posttest with a significance level of = 0.05 and it was concluded that there were differences in mathematical reasoning abilities between before and after distance learning based on e-learning. Meanwhile, the analysis of the questionnaire data shows that almost half of the students have a mathematical disposition after participating in e-learning-based Distance Learning.